IMPROVEMENT OF THE ORGANIZATIONAL AND ECONOMIC MECHANISM OF SMALL AND LARGE BUSINESSES IN CONSTRUCTION - Axmedova Nilufar Shuxratovna; Hajiboyeva Kamola Baxtiyor qizi (Western European Studies, 2025)
This article examines the organizational and economic mechanisms of small and large business entities operating in the construction sector, as well as the ways to improve these mechanisms. In addition, it analyzes the organizational, economic, and technological factors influencing the effective development of the industry. The construction sector, with its significant economic potential and the ability to participate directly in major infrastructure projects, constitutes an important component of the national economy. Therefore, enhancing modern organizational and economic mechanisms to ensure the stable and efficient operation of small and large business entities is considered a pressing task.
Keywords: Construction sector; small and large businesses; organizational-economic mechanisms